Financial, Absorption and Business Cycles in Selected African Countries - TCHIEUZING, Romuald Fernand AWOUTCHA; YAH, NEBA Cletus (International Journal of Social and Administrative Sciences, 2021)
This study examines the relationship between internal absorption, financial and business cycles in selected African countries. Using Markov’s regime change model on data for the period 1960-2018. The data was obtained from the online version of the World Bank’s World Development Indicators. The results show that the Keynesian or monetary effects on each phase of the business cycle is different in the various countries. During the phase of economic expansion, the rate of evolution of consumption and gross fixed capital formation accelerate the expansion trend. During the phase of recession, these variables play a stabiliser role by moderating the fall in real GDP. Liquidity ratio and nominal exchange rate affect the behaviour of real GDP in a mixed manner in both the phase of economic expansion and economic recession. These results show that economic policies should focus on household consumption and gross fixed capital formation to regulate the dynamics of the economy.